Analysis of Fairness Limit on Fuel Oil Consumption of Two-Tail Test Based Excavator and Dump Truck A Case Study in PT FK - Bella Puspa Octaviania; Supriyadi; Ambran Hartono (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2020)
A lack of method to find out the fairness limit of fuel consumption in mining operations enables statistical approach with two-tail test be applied to observe the fairness limit of actual fuel oil consumption compared to the manual handbook of its equipment. Fuel consumption according to the manual handbook for EXCA LIEBHERR 9350 excavator is 207.23 liters/hour and EXCA HITACHI 2500 is 191.51 liters/hour, while CATERPILLAR 777D Dump Truck is 36-53 liters/hour consider as low, 53-73, 8 liters/hour medium, and 73.8-96.5 liters/hour as high. This statistical approach has been carried out after fulfilling the concept of mechanized earth-moving. As a result, the differences in fuel consumption of LIEBHERR 9350 and HITACHI 2500 are 3.72% and 3.26%, which are still in range of a reasonable fuel consumption limit, while CAT 777D operating on LIEBHERR 9350 and CAT 777D operating on HITACHI 2500, each shows a difference in fuel consumption. The differences are 29.65%, meaning that it has exceeded the reasonable limits of fuel consumption and 7.15%, meaning that it is still in range of a reasonable fuel consumption limit.